One New C21 Steroidal Glycosides from the Leaves of Cynanchum hancockianum - Yu, Shubei; Lin, Xixi; Zheng, Yi; Wu, Zheng; Zheng, Wei; Qiao, Liman (Letters in Organic Chemistry, 2019)
C21 steroids glycosides of various deoxysugars have been emerging from genus of Cynanchum. Besides classical C21 glycosides, many C21 glycosides with seco-ring aglycones attracted the extensive attention of many researchers. We conducted a systematic chemical investigation on Cynanchum hancockianum, which led to the isolation of one new seco-ring C21 steroidal glycosides. The new compound was identified as cynaascyriogenin 3-O-β-D-glucopyranosyl-(1-4)-α-L-cymaropyranosy-(1-4)- β-D-cymaropyranosyl-(1-4)-β-D-cymaropyranoside. The cytotoxic activities of the compound were evaluated using the A549 and MCF-7 cell lines, respectively. The IC50 values of the compound were 41.3 and 67.1μM, respectively. This is the first report on the isolation of seco-ring C21 steroidal glycosides from Cynanchum hancockianum.
Keywords: deoxysugars